EKSISTENSI KAWASAN WISATA KULINER BANUA ANYAR KECAMATAN BANJARMASIN TIMUR KOTA BANJARMASIN PROVINSI KALIMANTAN SELATAN - Hermita, Hermita; Widaty, Cucu (Jurnal Tugas Akhir Mahasiswa Pendidikan Sosiologi, 2024)
The new Banua Culinary Tourism Area is an area developed by the city government and the local community in order to support tourism in the city of Banjarmasin. This study aims to find out what are the efforts in maintaining the existence of the Banua Anyar Culinary Tourism area and the obstacles in maintaining the existence of the Banua Anyar Culinary Tourism Area. The method used in this study is qualitative research method. The data sources selected using purposive sampling and informants in this study were 9 people. Data collection using observation, interview, and documentation techniques. Analysis of research results using data reduction steps, data presentation and data verification. Data validity testing is done by Extend Observation, Diligence In Research, Triangulation. Triangulation is divided into thre returns namely source triangulation, Enginering triangulation, and time triangulation. The results of the research Efforts in Maintaining the Existence of the Banua Anyar Culinary Tourism Area and Obstacles in Maintaining the Existence of the Banua Anyar Culinary Tourism Area. (1) Efforts to Maintain the Existence of Banua Anyar Culinary Tourism Area in Banjarmasin City, South Kalimantan Province, are divided into four, namely Efforts to maintain taste quality, Efforts to promote products, Efforts to maintain cleanliness, and Efforts to improve services. (2) Obstacles in maintaining the existence of the Banua Anyar culinary tourism area in Banjarmasin City, South Kalimantan province, namely competition betwen traders and climate change and the increase in raw materials.